78.3k views
4 votes
I'm confused. Can someone help me out with this problem step-by-step using the P = 2L + 2W formula?

I'm confused. Can someone help me out with this problem step-by-step using the P = 2L-example-1

1 Answer

1 vote

We can't use P = 2L + 2W because the sides have different lengths.

P = a + b + c + d

a = x

b = 2x

c = 2x - 2

d = x + 5

P = x + 2x + (2x - 2) + (x + 5)

P = x + 2x + 2x - 2 + x + 5

P = 6x + 3

if x = 4:

P = 6 ยท 4 + 3

P = 24 + 3

P = 27

User Axel Kemper
by
5.2k points